219k views
3 votes
Simplify x0y-3/x2y-1 A.1/x2y2 B. Y/x6 C. 4y3/x3 D.y3/2

User McGin
by
4.6k points

1 Answer

2 votes

Answer:

Option A)
(1)/(x^2y^2) is correct.

Therefore the simplified given expression
(x^0y^(-3))/(x^2y^(-1))=(1)/(x^2y^2)

Explanation:

Given expression is
(x^0y^(-3))/(x^2y^(-1))

To simplify the given expression:


(x^0y^(-3))/(x^2y^(-1))

Above expression can be written as


(x^0y^(-3))/(x^2y^(-1))=((1)y^(-3))/(x^2y^(-1))

(since
x^0=1 ,anything variable to the power "0' is 1)


(x^0y^(-3))/(x^2y^(-1))=(y^(-3))/(x^2y^(-1))


(x^0y^(-3))/(x^2y^(-1))=(1)/(x^2y^(-1)y^3) (since
a^(-m)=(1)/(a^m) )


(x^0y^(-3))/(x^2y^(-1))=(1)/(x^2y^(-1+3)) (using the property
a^m+a^n=a^(m+n))


(x^0y^(-3))/(x^2y^(-1))=(1)/(x^2y^2)

Therefore
(x^0y^(-3))/(x^2y^(-1))=(1)/(x^2y^2)

Therefore Option A)
(1)/(x^2y^2) is correct.

Therefore the simplified given expression
(x^0y^(-3))/(x^2y^(-1))=(1)/(x^2y^2)

User TomSawyer
by
4.7k points